Controle gerencial e análise de custos dos frigoríficos abatedouros de bovinos - Ferreira, Reginaldo Fernandes (2006)
This paper aims the construction of a managerial model to decision making based on the variable cost to the bovines slaughterhouse freezer developed into a conjoint production with the purpose of short term decision because of the industrial process speed. The development of this work starts approaching questions over the environment which involves the bovines slaughterhouse organizations in Brazil, demonstrating their functioning, economic aspects of this activity, and their importance in the Brazilian economy. Based on bibliography, it will be demonstrated the existent cost methodologies, their main concepts, the advantages and disadvantages of each one of them. The next stage, via bibliography research, it searches to characterize the conjoint production as a particular case predominantly of continuous production. It demonstrates its concepts, ways of cost appropriation more used, nevertheless, emphasizing its inadequate way to the decision making. This work developed practical cases so that are presented common operations to the activity, operations which lead, consequently, the company to the necessity of a decision making. To the decision making, it is adopted the variable cost which will be taken as a base on the contribution margin. Besides the contribution margin, others decisions are taken based on incremental contribution margin because of the separation point that obligates to be considered only the incremental costs and revenues. This work shows a defined point in which the concepts presented by the researched bibliography are not possible to be applied on the decision making over the cost analysis in practice in the bovines slaughterhouses. Based on the contribution margins and fixed costs, this paper also points out how the decision makings can be taken over the minimum quantity of heads of cattle that the slaughterhouse freezer must slaughter and the minimum of pieces to bone and export